Augustine and John’s Gospel from Conversion to Confessiones - Cameron, Michael (Augustinian studies, 2017)
How did John’s Gospel draw and compel Augustine before and during the composition of Confessiones? Analyzing references to John in Augustine’s works from his embrace of Nicene Christianity to the writing of Confessiones, this paper finds a growing (and Johannine-based) emphasis on the importance of Christ’s humanity. Augustine strategically invokes two texts in Confessiones’ crucial seventh book: John 1:14, "the Word was made flesh," and John 14:6, "I am the way, the truth, and the life." This paper considers three features: First, how the rhetorical device of anticipation (prolepsis) allows Augustine simultaneously to unify his developing Christological perspective and to build drama into his conversion narrative. Second, how the structure of Confessiones, which first works to understand divine transcendence and then seeks to relate that divine transcendence back to time, emphasizes the central role played by the Gospel of John in advancing Augustine’s conversion story. Third and finally, how invocations of John’s Gospel typify the way that, for the Augustine of Confessiones, reading scripture had become the means of achieving new spiritual self-comprehension. Texts from John were not mere receptors or reflectors of spiritual forces that moved Augustine toward conversion, but, rather, powerful agents of conversion in their own right.